EDUKASI AKSI BERGIZI UPAYA PENCEGAHAN ANEMIA PADA REMAJA - Chyka Febria; Mega Ade Nugrahmi; Kartika Mariyona (MONSU'ANI TANO Jurnal Pengabdian Masyarakat, 2023)
The incidence of anemia in West Sumatra province reached a national average of 14.8% according to the Minister of Health's Decree of 29.8% in women and 27.6% in men. West Sumatra Province is the 4th province with the highest incidence of anemia after Maluku, Southeast Sulawesi and Gorontalo (Rikesdas, 2018). The aim of this activity is to increase knowledge and motivate participants to apply balanced nutrition guidelines and apply the contents of my plate in their daily lives. The method used is to provide education about the contents of my plate to young women, by giving pretest and posttest questionnaires. The results of this activity after education was carried out increased knowledge about the contents of my plate and teenagers already knew how much to eat in one meal. The conclusion from this activity was that when the pre-test was carried out, the majority of female students had poor knowledge, namely 34 people (68%), and after being given education, the results of the post-test showed that the majority of female students had good knowledge, 38 people (76%).